1978
DOI: 10.1007/bf00284771
|View full text |Cite
|
Sign up to set email alerts
|

A further case of a 22;22 Robertsonian translocation associated with recurrent abortions

Abstract: A case of 22;22 Robertsonian translocation, identified in the husband of a woman who had five early abortions, is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…These 20 couples generated 28 fetuses with unbalanced chromosome constitutions, but none of them had trisomy 22. In contrast, studies of recurrent abortions have led to the detection of 22/22 and 141 22 familial translocations [Mameli et al, 1978;Fried et al, 19741. Thus, there is ample evidence that trisomy 22, except when mosaic, is exceptional beyond the first trimester of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…These 20 couples generated 28 fetuses with unbalanced chromosome constitutions, but none of them had trisomy 22. In contrast, studies of recurrent abortions have led to the detection of 22/22 and 141 22 familial translocations [Mameli et al, 1978;Fried et al, 19741. Thus, there is ample evidence that trisomy 22, except when mosaic, is exceptional beyond the first trimester of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…This patient suggested the possibility that trisomy for genes on chromosome 22, especially distal to q13.1, could cause partial sex reversal. The haplo‐insufficiency for ribosomal genes from p13‐tel is unlikely to be causal and sexual ambiguity has not been reported with homozygosity for such deletions [Mameli et al, 1978].…”
Section: Introductionmentioning
confidence: 99%
“…This patient suggested the possibility that trisomy for genes on chromosome 22, especially distal to q13.1, could cause partial sex reversal. The haplo-insufficiency for ribosomal genes from p13-tel is unlikely to be causal and sexual ambiguity has not been reported with homozygosity for such deletions [Mameli et al, 1978]. Phelan et al [2003] recently reported a patient with velocardiofacial syndrome who was found to be a 46,XX male.…”
mentioning
confidence: 96%